Evaluation of Bacteriological Characteristics and Antibiotic Use in the Treatment of Bloodstream Infections in COVID-19 Patients in the Intensive Care Unit of a COVID-19 Treatment Hospital - Thi Huong Thao, Bui; Viet Anh, Nguyen; Bui Hai, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 3, 2025)
This study aimed to evaluate the microbial etiology and use of empiric antibiotics in the treatment of septicemia in patients with COVID-19 at the Intensive Care Unit, the COVID-19 Treatment Hospital. This study involved a descriptive analysis of 87 patients. The results showed that most cases treated in the ICU for COVID-19 were patients with severe to critical COVID-19 infection. Blood culture results revealed that 79.3% of isolated bacteria were Gram-negative, with two main bacteria, including Acinetobacter baumannii and Klebsiella pneumonia . The antibiogram showed resistance to most antibiotics. The indicated antibiotics were broad-spectrum bactericidal antibiotics and targeted to Gram-negative bacteria. The rate of appropriate antibiotic use increased from 39.1% to 52.3% after the results of the antibiogram. The proportion of patients who received appropriate antibiotics in the group of surviving patients was higher than that in the group of patients who died. However, this difference was not statistically significant.